Characteristics of audit committees and public accountants on audit fees - Shelsa Aulia Yovanka; Vita Elissa Fitriana (President University Press, 2022)
The purpose of this research is to obtain empirical what are factors that affect audit fees with audit fees as dependent variable and audit committee effectiveness as independent variable. This research uses manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020 period. Data analysis was carried out using multiple regression analysis, with a selected sample of 198 companies of three years observation. The results indicates that audit committee size influence audit fees, while audit committee meeting and audit committee expertise are not influence audit fees. Therefore, company could focus on aspects which can influence the audit fees.